ZnO-based nanometer doped material, preparation method thereof and QLED device
By doping elements in ZNO, adjusting the mixed concentration and energy level position, the problem of imbalance and excitement in the QLED device in the QLED device has achieved higher external quantum efficiency and longer working life span Essence
Patent Information
- Application Number
- CN202411513039.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-24
AI Technical Summary
The presence of charge injection imbalance caused by energy level mismatch in QLED devices and exciton quenching caused by non-radiative recombination center and interface charge transfer process caused by ZnO's abundant defect level, limiting the improvement of device performance.
By doping lanthanide elements such as Nd, Gd, Eu, and Er into ZnO, the doping concentration and energy level position are controlled, the electron injection barrier is increased, the carrier injection is balanced, and the defect states of ZnO are reduced, thereby improving the electron transport layer performance.
Effectively reduce the fluorescence ingenuity caused by the contact between the electronic transport layer and the luminous layer, regulate the electrons to balancing the injecting, improve the external quantum efficiency of the QLED device, and improve the brightness and work life.
Smart Images

Figure CN119364997A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of optoelectronic materials, and in particular relates to a ZnO-based nano-doped material and a preparation method thereof, and a QLED device. Background Art
[0002] As we all know, quantum dots have the advantages of narrow half-width (FWHM), continuously adjustable color, and high fluorescence quantum yield. Therefore, compared with traditional light-emitting devices LED and OLED, quantum dot light-emitting diodes have the advantages of high stability, high color purity, and continuously adjustable emission color. Quantum dot light-emitting diodes (QLEDs) can be a potential candidate for the next generation of displays. However, QLEDs still have some problems, such as the charge injection imbalance caused by energy level mismatch, which causes Auger recombination caused by quantum dot charging, and the exciton quenching caused by the spontaneous interfacial charge transfer process at the interface of ZnO / QDs due to the rich defect energy levels of ZnO. These problems restrict the performance improvement of QLED devices.
[0003] The existing technology proposes to modify the electron transport layer by adding intercalation, anion doping, coating, cation doping and other methods, which can effectively balance the injection of electrons and holes, confine them to the QDs layer, promote radiative recombination, and ultimately achieve improved device efficiency. Various doping methods can effectively balance the injection of electrons and holes, inhibit QDs charging, reduce non-radiative recombination, and ultimately prepare devices with excellent performance. However, the current technical solutions still have shortcomings. For green quantum dot devices, electron injection is still relatively fast, the electron injection of the light-emitting layer is unbalanced, ion doping is insufficient to suppress the internal defect states of ZnO, and the problem of device efficiency roll-off all affect the device performance; and the inert intercalation increases the complexity of the device and introduces new interface problems, which is not conducive to research on device performance improvement.
[0004] Based on this, a ZnO-based modified material is needed to optimize the electron transport performance of ZnO nanocrystalline thin films and the overall device stability. Summary of the invention
[0005] One of the purposes of the present invention is to provide a ZnO-based nano-doped material. The ZnO-based nano-doped material provided by the present invention can effectively regulate the doping concentration of Nd, Gd, Eu, and Er through doping, regulate the energy level position, increase the electron injection barrier, balance the carrier injection, reduce the ZnO defect state, weaken the electron transmission ability, improve the unbalanced problem of carrier injection in which the electron transmission is more than the hole, reduce the charging of quantum dots, and effectively increase the radiation recombination efficiency.
[0006] To achieve the above object, the present invention adopts the following technical solutions:
[0007] A ZnO-based nano doped material comprises ZnO and a lanthanide element doped in the ZnO; the lanthanide element is any one of Nd, Gd, Eu and Er; and the amount of the lanthanide element in the ZnO-based nano doped material accounts for 1-15%.
[0008] Preferably, the amount of Nd in the ZnO-based nano-doping material accounts for 7-12%, the amount of Gd in the ZnO-based nano-doping material accounts for 1-3%, the amount of Eu in the ZnO-based nano-doping material accounts for 3-8%, and the amount of Er in the ZnO-based nano-doping material accounts for 12-15%.
[0009] Preferably, the amount of Nd in the ZnO-based nano-doping material accounts for 10%, the amount of Gd in the ZnO-based nano-doping material accounts for 1%, the amount of Eu in the ZnO-based nano-doping material accounts for 5%, and the amount of Er in the ZnO-based nano-doping material accounts for 15%.
[0010] Preferably, the average particle size of the ZnO-based nano-doping material is 3 to 6 nm.
[0011] More preferably, the average particle size of the ZnO nanomaterial is 3.5 to 4 nm. The present invention can strictly control the average particle size of the material within the above range, so that the particles are more uniform, the nanometer level has a larger surface area, the particles are more fully contacted, the roughness when forming a thin film is reduced, and the film layer is more uniform and dense when used as an electron transport layer material.
[0012] The second object of the present invention is to provide a method for preparing a ZnO-based nano doped material. The method can ensure that the prepared doped material based on ZnO nanoparticles has a more complete structure and more uniform grains, and the preparation process is simple, the parameters are easy to control, and the cost is low.
[0013] To achieve the above object, the present invention adopts the following technical solutions:
[0014] The preparation method of the above-mentioned ZnO-based nano-doped material comprises the following steps: uniformly mixing a zinc salt solution and a lanthanide compound solution, then adding an alkali solution to stir and react, and after the reaction is completed, adding a precipitant to the reaction solution and centrifuging to obtain the material; the lanthanide compound is any one of a neodymium compound, a gadolinium compound, a europium compound, and an erbium compound.
[0015] Preferably, the molar ratio of the zinc salt to the lanthanide compound is 99:1 to 85:15; - The molar ratio is 1:0.5~4.
[0016] More preferably, the molar ratio of the zinc salt to the neodymium compound is 90:10; the molar ratio of the zinc salt to the gadolinium compound is 99:1; the molar ratio of the zinc salt to the europium compound is 95:5; and the molar ratio of the zinc salt to the erbium compound is 85:15.
[0017] Preferably, the neodymium compound is at least one of neodymium sulfate, neodymium chloride, neodymium nitrate, neodymium acetate, and neodymium acetylacetonate; the gadolinium compound is at least one of gadolinium sulfate, gadolinium chloride, gadolinium nitrate, gadolinium acetate, and gadolinium acetylacetonate; the europium compound is at least one of europium sulfate, europium chloride, europium nitrate, europium acetate, and europium acetylacetonate; the erbium compound is at least one of erbium sulfate, erbium chloride, erbium nitrate, erbium acetate, and erbium acetylacetonate.
[0018] Preferably, the concentration of the zinc salt solution is 0.01 to 0.2 mol / L, the concentration of the lanthanide compound solution is 0.01 to 0.2 mol / L, and the concentration of the alkali solution is 0.1 to 2 mol / L.
[0019] More preferably, the concentration of the alkali solution is 0.3-0.8 mol / L. The present invention can improve the degree of hydrolysis of the soluble zinc salt by controlling the concentrations of hydroxide ions in the alkali solution and zinc ions in the soluble zinc salt within the above range, thereby making the hydrolysis more complete.
[0020] Preferably, the zinc salt is any one of zinc acetate, zinc nitrate, zinc chloride, zinc sulfate, zinc acetylacetonate, and zinc gluconate; the solvents of the zinc salt solution and the lanthanide compound solution are any one of dimethyl sulfoxide, ethanol, n-heptane, and ethyl acetate; and the alkali solution is any one of potassium hydroxide solution, sodium hydroxide solution, ammonia water, and tetramethylammonium hydroxide solution.
[0021] Preferably, the stirring reaction temperature is 10-30° C., and the stirring reaction time is 1-3 hours. The present invention can make the obtained nanoparticles have better crystallinity by controlling the reaction temperature and time within the above range.
[0022] More preferably, the precipitant is preferably a mixed solution of anhydrous ethanol and n-heptane; the mass ratio of anhydrous ethanol to n-heptane is preferably 5:95 to 50:50, more preferably 10:90 to 25:70. The present invention controls the mass ratio of anhydrous ethanol to n-heptane within the above range, which is more conducive to the sufficient precipitation of ZnO-based nano-doped materials in the mixed solution, thereby obtaining ZnO-based nano-doped materials with good crystallinity.
[0023] The third object of the present invention is to provide a QLED device. The present invention uses the ZnO-based nano-doped material prepared by the above preparation method as the QLED electron transport layer to construct a green quantum dot light-emitting diode, which can effectively reduce the fluorescence quenching caused by the contact between the electron transport layer and the light-emitting layer, regulate the electron injection balance, and thus improve the external quantum efficiency of the QLED device, so that the performance of the QLED device is significantly improved in brightness and efficiency, and at the same time can increase the working life of the QLED device.
[0024] The QLED device of the present invention comprises, from the lower layer to the upper layer, an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer and a cathode; the electron transport layer is made of the above-mentioned ZnO-based nano-doped material.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The present invention provides a ZnO-based QLED electron transport layer. Experimental results show that the ZnO-based QLED electron transport layer provided by the present invention is characterized by XPS, AFM, and steady-state transient fluorescence, indicating that the ZnO-based QLED electron transport layer can effectively inhibit the surface defect state of ZnO (hydroxyl group, oxygen vacancy), thereby weakening the fluorescence quenching of ZnO to QDs, increasing the radiation recombination efficiency of quantum dots, and is beneficial to improving the brightness and external quantum efficiency of QLED devices. The test results of UPS, C-AFM and single-carrier devices show that the carrier mobility of the ZnO-based QLED electron transport layer is reduced, and the electron transport capacity is weakened, which is beneficial to balanced carrier injection.
[0027] 2. The present invention provides a QLED device. The green QLED device is assembled using the ZnO-based nano-doped material provided by the present invention as an electron transport layer, which can effectively reduce the fluorescence quenching caused by the contact between the electron transport layer and the light-emitting layer, and regulate the electron injection balance, thereby improving the external quantum efficiency of the QLED device and increasing the device's service life. When the Nd doping ratio is 10%, the Gd doping ratio is 1%, the Eu doping ratio is 5%, and the Er doping ratio is 15%, the device performance is greatly improved. For example, in a certain embodiment of the present invention, compared with the control device, the brightness is increased by 48.72%, and the device EQE is increased from 14.88% to 24.39%, an increase of 63.91%. At the same time, the device T 50 The service life is increased from 1739.79h to 8229.93h. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A schematic diagram of the device structure of a QLED provided by the present invention;
[0029] Figure 2XRD diagrams of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention;
[0030] Figure 3 UV-vis graphs of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention;
[0031] Figure 4 PL spectra of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention;
[0032] Figure 5 TEM image of the nanomaterial sample provided in Comparative Example 1 of the present invention;
[0033] Figure 6 TEM image of the nanomaterial sample provided in Example 1 of the present invention;
[0034] Figure 7 HRTEM image of the nanomaterial sample provided in Comparative Example 1 of the present invention;
[0035] Figure 8 HRTEM image of the nanomaterial sample provided in Example 1 of the present invention;
[0036] Fig. 9 AFM images of nanomaterial samples provided in Comparative Example 1 and Example 1 of the present invention;
[0037] Fig.10 O1s XPS spectrum of the nanomaterial sample provided in Comparative Example 1 of the present invention;
[0038] Fig.11 The O1s XPS spectrum of the nanomaterial sample provided in Example 1 of the present invention;
[0039] Fig.12 The O1s XPS spectrum of the nanomaterial sample provided in Example 2 of the present invention;
[0040] Fig.13 The O1s XPS spectrum of the nanomaterial sample provided in Example 3 of the present invention;
[0041] Fig.14 The O1s XPS spectrum of the nanomaterial sample provided in Example 4 of the present invention;
[0042] Fig.15 UPS spectra of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention at 19.0 to 16.0 eV;
[0043] Fig.16 UPS spectra of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention at 6.0 to 3.0 eV;
[0044] Fig.17 The (αhν) of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention at 3.4 to 4.0 eV 2 -hν curve spectrum;
[0045] Fig.18 JV characteristic curves of single-type carrier devices of nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention;
[0046] Fig.19 Steady-state fluorescence spectra obtained by testing the quantum dot fluorescence quenching effect of the composite board samples provided in Test Examples 1 to 8 of the present invention;
[0047] Fig. 20 Transient fluorescence spectra obtained by testing the quantum dot fluorescence quenching effect of the composite board samples provided in Test Examples 1 to 8 of the present invention;
[0048] Fig.21 The current density-voltage-brightness characteristic curves of the QLED devices of Comparative Example 4 and Examples 5 to 8 of the present invention;
[0049] Fig. 22 The current efficiency-brightness-external quantum efficiency characteristic curves of the QLED devices of Comparative Example 4 and Examples 5 to 8 of the present invention;
[0050] Fig.23 It is a comparison chart of the brightness attenuation curves of the QLED devices of Comparative Example 4 and Examples 5 to 8 of the present invention. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further explained below in conjunction with specific embodiments, comparative examples, test examples and drawings.
[0052] In the following examples, comparative examples and test examples, the raw materials and preparation methods used are conventional materials and techniques in the art unless otherwise specified.
[0053] Example 1
[0054] A ZnO-based nano doping material comprises ZnO and a lanthanide element Nd doped in the ZnO, wherein the amount of Nd in the ZnO-based nano doping material accounts for 10%.
[0055] The method for preparing the above-mentioned ZnO-based nano-doped material comprises the following steps:
[0056] Take 2.7mmol zinc acetate and 0.3mmol neodymium acetate and add them to dimethyl sulfoxide respectively to obtain 0.1mol / L zinc acetate solution and 0.1mol / L neodymium acetate solution. Stir the two solutions at 20℃ for 30min. Add the neodymium acetate solution to the zinc acetate solution at a molar ratio of 90:10 and continue stirring for 15min to obtain a mixed solution. 2+ With tetramethylammonium hydroxide OH - The molar ratio of is 3:5, the mixed solution is added into a 0.55 mol / L tetramethylammonium hydroxide ethanol solution, and the reaction is stirred at 20°C for 2h; anhydrous ethanol / n-heptane mixed solvent with a mass ratio of 10:90 is added to the reaction solution, and the mixture is centrifuged to obtain the ZnO-based nano-doped material, which is named NdZnO (Nd: 10%).
[0057] Example 2
[0058] A ZnO-based nano doped material comprises ZnO and a lanthanide element Gd doped in the ZnO, wherein the amount of Gd in the ZnO-based nano doped material accounts for 1%.
[0059] The method for preparing the above-mentioned ZnO-based nano-doped material comprises the following steps:
[0060] 1.98mmol zinc nitrate and 0.2mmol gadolinium nitrate were added to ethanol to obtain 0.2mol / L zinc nitrate solution and 0.2mol / L gadolinium nitrate solution, respectively. The two solutions were stirred at 15°C for 30min. The gadolinium nitrate solution was added to the zinc nitrate solution at a molar ratio of 99:1 and stirred for 15min to obtain a mixed solution. 2+ With tetramethylammonium hydroxide OH - The molar ratio of the mixed solution is 1:4, the mixed solution is added into a 0.8 mol / L tetramethylammonium hydroxide ethanol solution, the reaction is stirred at 15°C for 2 h, and anhydrous ethanol / n-heptane mixed solvent with a mass ratio of 15:85 is added to the reaction solution to obtain the ZnO-based nano-doped material, which is named GdZnO (Gd: 1%).
[0061] Example 3
[0062] A ZnO-based nano doped material comprises ZnO and a lanthanide element Eu doped in the ZnO, wherein the amount of Eu in the ZnO-based nano doped material accounts for 5%.
[0063] The method for preparing the above-mentioned ZnO-based nano-doped material comprises the following steps:
[0064] Take 1.9mmol zinc chloride and 1mmol europium chloride and add them to water to obtain 0.05mol / L zinc chloride solution and 0.05mol / L europium chloride solution, respectively. Stir the two solutions at 20℃ for 30min. Add europium chloride solution to zinc chloride solution at a molar ratio of 95:5 and continue stirring for 15min to obtain a mixed solution. 2+ With tetramethylammonium hydroxide OH - The molar ratio of is 1:2, the mixed solution is added into tetramethylammonium hydroxide ethanol solution (0.3 mol / L), and the reaction is stirred at 10°C for 3 h. Anhydrous ethanol / n-heptane mixed solvent with a mass ratio of 20:80 is added to the reaction solution to obtain EuZnO (Eu: 5%).
[0065] Example 4
[0066] A ZnO-based nano doped material comprises ZnO and a lanthanide element Er doped in the ZnO, wherein the amount of Er in the ZnO-based nano doped material accounts for 15%.
[0067] The method for preparing the above-mentioned ZnO-based nano-doped material comprises the following steps:
[0068] Take 3.4mmol of zinc acetylacetonate and 0.6mmol of erbium acetylacetonate and add them to acetone to obtain 0.15mol / L zinc acetylacetonate solution and 0.15mol / L erbium acetylacetonate solution, respectively. Stir the two solutions at 20℃ for 30min. Add erbium acetylacetonate solution to zinc acetylacetonate solution at a molar ratio of 85:15, and continue stirring for 15min to obtain a mixed solution; press Zn 2+ With tetramethylammonium hydroxide ethanol solution OH - The molar ratio of is 1:0.5, the mixed solution is added into tetramethylammonium hydroxide ethanol solution (0.65 mol / L), and the reaction is stirred at 20°C for 2 h. Anhydrous ethanol / n-heptane mixed solvent with a mass ratio of 25:75 is added to the reaction solution to obtain ErZnO (Er: 15%).
[0069] Example 5
[0070] A QLED device having a structure as follows Figure 1 As shown, from bottom to top, they are: anode (ITO substrate), hole injection layer (PEDOT:PSS), hole transport layer (TFB), light-emitting layer (QDs), electron transport layer (ETL) and cathode (Al); wherein the electron transport layer is the ZnO-based nano-doped material provided in Example 1. Figure 1 The structure of the QLED device shown can be abbreviated as ITO / PEDOT:PSS / TFB / QDs / ETL / Al.
[0071] The specific preparation method of the above QLED device is as follows:
[0072] (1) Anode pretreatment: clean the ITO glass substrate, scrub with detergent and then ultrasonicate for 20 minutes, then ultrasonicate with deionized water, acetone and isopropanol for 15 minutes, and then treat with UV-ozone for 15 minutes to obtain a clean ITO substrate with a thickness of 200 nm;
[0073] (2) Coating a hole injection layer: Spin-coat a mixture of poly (3,4-ethylenedioxythiophene) / polystyrene sulfonic acid on an ITO substrate at 5000 rpm, wipe out the electrode with a cotton swab dipped in water, place on an annealing plate and anneal at 130° C. for 15 minutes to form a hole injection layer (10 nm thick), thereby obtaining a composite substrate I;
[0074] (3) Coating a hole transport layer: The composite substrate I obtained in step (2) was transferred to a glove box filled with nitrogen, 40 μL of a 8 mg / mL TFB chlorobenzene solution was taken and spin-coated at 3000 rpm on the surface of the hole injection layer of the composite substrate I, and annealed at 150° C. for 30 minutes, and naturally cooled to room temperature to form a hole transport layer (thickness of 40 nm), thereby obtaining a composite substrate II;
[0075] (4) coating the light-emitting layer: spin-coating 18 mg / mL of green quantum dots (whose structure is ZnCdSeS / ZnS) in n-octane solution at 3000 rpm on the surface of the hole transport layer of the composite substrate II to form a film, and naturally leaving it to dry to form a light-emitting layer (thickness of 40 nm), thereby obtaining a composite substrate III;
[0076] (5) Coating an electron transport layer: The ZnO-based nano-doping material provided in Example 1 was dispersed in an ethanol solution (concentration of 30 mg / mL), and the solution was spin-coated at 3000 rpm on the surface of the light-emitting layer of the composite substrate III to form a film. Then, the edge of the substrate was wiped with a cotton swab dipped in a small amount of chlorobenzene to expose the electrode, and the substrate was annealed at 60° C. for 30 minutes, and then naturally cooled to room temperature to form an electron transport layer (thickness of 100 nm), thereby obtaining a composite substrate IV.
[0077] (6) Depositing the cathode: The composite substrate IV obtained in step (5) is transferred to a high vacuum deposition chamber with a vacuum degree of ≤5×10-6 Mbar, and an aluminum electrode (thickness of 300 nm) is deposited as a cathode by a conventional evaporation method. Two to three drops of UV curing glue are added to the center of the cathode surface. A cover glass is placed on the surface to remove bubbles. The UV curing glue is cured by irradiating with a UV lamp for 3 minutes to obtain a QLED device.
[0078] Example 6
[0079] A QLED device is basically the same as Example 5, except that the electron transport layer is made of the ZnO-based nano-doped material provided in Example 2.
[0080] Example 7
[0081] A QLED device is basically the same as Example 5, except that the electron transport layer is made of the ZnO-based nano-doped material provided in Example 3.
[0082] Example 8
[0083] A QLED device is basically the same as Example 5, except that the electron transport layer is made of the ZnO-based nano-doped material provided in Example 4.
[0084] Comparative Example 1
[0085] This comparative example 1 provides a ZnO nanomaterial, and the preparation method thereof is as follows: zinc acetate is added into a dimethyl sulfoxide solvent to obtain a zinc acetate solution with a molar concentration of 0.1 mol / L; 2+ With tetramethylammonium hydroxide OH - The zinc acetate solution is added to an ethanol solution of tetramethylammonium hydroxide with a molar ratio of 3:5, and the reaction is stirred at 20°C for 2h; an anhydrous ethanol / n-heptane mixed solvent with a mass ratio of 10:90 is added to the reaction solution, and the mixture is centrifuged to obtain a ZnO nanomaterial, which is recorded as ZnO.
[0086] Comparative Example 2
[0087] The present comparative example 2 provides a Nd2O3ZnO nanomaterial, and the preparation method thereof is as follows: zinc acetate is added to a dimethyl sulfoxide solvent to obtain a zinc acetate solution with a molar concentration of 0.1 mol / L; neodymium oxide is added to a dimethyl sulfoxide solvent to obtain a neodymium oxide solution with a molar concentration of 0.1 mol / L, the two solutions are stirred at 20°C for 30 minutes, an appropriate amount of neodymium oxide solution is added to the zinc acetate solution at a molar ratio of 90:10, and stirring is continued for 15 minutes to obtain a mixed solution; and ZnO is added to the zinc acetate solution at a molar ratio of 0.1 mol / L. 2+ 、Nd 3+ With tetramethylammonium hydroxide OH - The molar ratio of 3:5 was added to the mixed solution into an ethanol solution of tetramethylammonium hydroxide with a concentration of 0.55 mol / L, and the mixture was stirred at 20°C for 2 h; anhydrous ethanol / n-heptane mixed solvent with a mass ratio of 10:90 was added to the reaction solution, and the mixture was centrifuged to obtain Nd2O3ZnO nanomaterials, recorded as Nd2O3ZnO (Nd2O3: 10%).
[0088] Comparative Example 3
[0089] The present comparative example 3 provides a LaZnO nanomaterial, and the preparation method thereof is as follows: zinc acetate is added to a dimethyl sulfoxide solvent to obtain a zinc acetate solution with a molar concentration of 0.1 mol / L; lanthanum acetate is added to a dimethyl sulfoxide solvent to obtain a lanthanum acetate solution with a molar concentration of 0.1 mol / L, the two solutions are stirred at 20° C. for 30 min, an appropriate amount of lanthanum acetate solution is added to the zinc acetate solution at a molar ratio of 90:10, and stirring is continued for 15 min to obtain a mixed solution; Zn 2+ ,La 3+ With tetramethylammonium hydroxide OH - The molar ratio of the mixed solution is 3:5, and the mixed solution is added into an ethanol solution of tetramethylammonium hydroxide with a concentration of 0.55 mol / L, and the reaction is stirred at 20°C for 2 hours; anhydrous ethanol / n-heptane mixed solvent with a mass ratio of 10:90 is added to the reaction solution, and the mixture is centrifuged to obtain LaZnO nanomaterial, which is recorded as LaZnO (La: 10%).
[0090] Comparative Example 4
[0091] A QLED device is basically the same as Example 5, except that the electron transport layer is made of the ZnO nanomaterial provided in Comparative Example 1.
[0092] Comparative Example 5
[0093] A QLED device is basically the same as Example 5, except that the electron transport layer is made of the ZnO nanomaterial provided in Comparative Example 2.
[0094] Comparative Example 6
[0095] A QLED device is basically the same as Example 5, except that the electron transport layer is made of the ZnO nanomaterial provided in Comparative Example 3.
[0096] Test Example 1
[0097] In order to explore the differences in structure and performance between the ZnO-based nano-doped materials obtained in Examples 1 to 4 and the ZnO nano-material obtained in Comparative Example 1, the above samples were subjected to structural characterization and performance testing.
[0098] (1) XRD test
[0099] XRD test was performed on the ZnO-based nano-doped materials obtained in Examples 1 to 4 and the ZnO nano-material obtained in Comparative Example 1. The results are as follows: Figure 2 shown.
[0100] Depend on Figure 2From the results shown, it can be seen that the above-mentioned test samples all show 7 characteristic peaks, indicating that the doping of neodymium, gadolinium, europium and erbium will not change the hexagonal wurtzite structure of ZnO nanoparticles. At the same time, the position of the diffraction peak has basically not changed, indicating that there is no obvious lattice distortion and the obtained material still has good crystallinity.
[0101] (2) UV-vis test
[0102] The ZnO-based nano-doped materials (collectively named LnZnO) obtained in Examples 1 to 4 and the ZnO nano-material obtained in Comparative Example 1 were subjected to UV-vis detection, and the obtained UV-vis spectra were as follows: Figure 3 shown.
[0103] Depend on Figure 3 It can be seen that, compared with ZnO in Comparative Example 1, the doping of lanthanide elements in the LnZnO nanoparticles provided in Examples 1 to 4 causes an obvious blue shift in the absorption edge and an increase in the band gap, which indicates that the ZnO-based nano-doped material can finely change the band gap compared with ZnO in Comparative Example 1.
[0104] (3) Photoluminescence test
[0105] The photoluminescence (PL) spectrum of the ZnO-based nano-doped materials LnZnO materials obtained in Examples 1 to 4 and the ZnO nano-material obtained in Comparative Example 1 was tested. The obtained PL spectrum is as follows: Figure 4 shown.
[0106] from Figure 4 It is obvious that ZnO has two emission peaks. The ultraviolet emission peak at 375nm corresponds to the intrinsic emission peak of ZnO. After normalizing the intrinsic peak, the defect peak emission intensity in the visible light region of 500-550nm is compared. It is found that compared with ZnO in Comparative Example 1, the defect peak intensity of Examples 1-4 samples is significantly reduced, indicating a reduction in ZnO defect states. At the same time, the position of the defect emission peak changes slightly, indicating that the type of emission defect may have changed. This shows that doping can effectively suppress ZnO defect states.
[0107] (4) TEM test
[0108] The ZnO-based nano-doped material LnZnO material obtained in Example 1 and the ZnO nano-material obtained in Comparative Example 1 were subjected to TEM testing, and the TEM images obtained were as follows: Figure 5 and 6 shown.
[0109] Depend on Figure 5 , 6It can be seen that the nanoparticles of each sample are dispersed in anhydrous ethanol and have good dispersibility. In addition, from the morphology of a single ZnO nanoparticle, the ZnO provided by Comparative Example 1 and the nanoparticles provided by Example 1 are both spherical and the morphology has not changed. The particle size change was measured, and the particle size of Comparative Example 1 was 3.62nm, and the particle size of Example 1 was 3.77nm, and the particle size increased slightly.
[0110] (5) HRTEM test
[0111] The ZnO-based nano-doped material (LnZnO material) obtained in Example 1 and the ZnO nano-material obtained in Comparative Example 1 were subjected to HRTEM testing, and the HRTEM images obtained were as follows: Figure 7 and 8 shown.
[0112] Figure 7 , 8 The image clearly shows lattice fringes. Through DM software processing, it is found that the crystal plane spacing of comparative example 1 is about 0.247 nm, and the crystal plane spacing of embodiment 1 is about 0.255 nm, both corresponding to the (101) crystal plane.
[0113] (6) AFM test
[0114] The ZnO-based nano-doped material LnZnO material obtained in Example 1 and the ZnO nano-material obtained in Comparative Example 1 were subjected to AFM testing. The AFM images obtained by the test are as follows: Fig. 9 As shown. Fig. 9 (a) is the AFM image of Comparative Example 1. Fig. 9 (b) is the AFM image of Example 1. The image results show that compared with the ZnO film, the roughness of the LnZnO film prepared in Example 1 is slightly reduced and the film morphology is improved.
[0115] (7)XPS test
[0116] XPS test was performed on the ZnO-based nano-doped LnZnO material obtained in Examples 1 to 4 and the ZnO nano-material obtained in Comparative Example 1. The XPS spectra obtained are as follows: Figures 10 to 14 shown.
[0117] It is obvious from the O1s core energy level spectrum of the nano-sample of Comparative Example 1 that O 1s can be divided into three peaks, which are 529.9±0.1eV (O M )、531.7±0.1eV(O V ) and 532.3±0.1eV(O H ) is the center. M That is, O-Zn bonding, O V and O HThe peaks are attributed to oxygen vacancies and hydroxyl oxygen, which are collectively referred to as surface defects. After doping, the O1s peaks were separated and only two peaks were fitted, namely 529.9±0.1eV (O M )、531.7±0.1eV(O V ), indicating that the surface defect states of ZnO NPs are passivated, thereby affecting the generation of free carriers, and further affecting the electron mobility and the electrical properties of the oxide semiconductor. With the increase of doping amount, the oxygen vacancy defect shows a decreasing trend, indicating that the surface defects of ZnO are effectively suppressed.
[0118] (8)UPS test
[0119] The electronic structures of the ZnO-based nano-doped LnZnO materials obtained in Examples 1 to 4 and the ZnO nano-material samples obtained in Comparative Example 1 were subjected to UPS testing, and the obtained UPS spectra were as follows: Fig.15 , 16 shown.
[0120] in, Fig.15 UPS spectra (secondary electron cutoff edge) of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention at 19.0 to 16.0 eV; Fig.16 UPS spectra of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention at 6.0 to 3.0 eV (Fermi level edge). The above spectrum results show that the downward shift of the conduction band position of LnZnO nanoparticles may increase the injection of electrons, and the downward shift of the valence band position effectively blocks the leakage of holes from the quantum dot layer to the electron transport layer, increasing the radiative recombination of quantum dots.
[0121] (9) Band gap calculation
[0122] The ZnO-based nano-doped materials LnZnO materials obtained in Examples 1 to 4 and the ZnO nano-materials obtained in Comparative Example 1 were subjected to UV-vis testing, and the (αhν) obtained by conversion was 2 -hν curve diagram Fig.17 As shown in the figure, the band gap sizes of the nanomaterial samples provided in Comparative Example 1 and Examples 1 to 4 of the present invention are obtained from the range of 3.4 to 4.0 eV. Compared with Comparative Example 1, the band gaps of the nanomaterial samples provided in Examples 1 to 4 are significantly larger.
[0123] (10) Current density-voltage (JV) characteristic test
[0124] The ZnO-based nano-doped material LnZnO material obtained in Examples 1 to 4 of the present invention and the ZnO nano-material obtained in Comparative Example 1 were respectively prepared into single-carrier (electronic) devices, and the device structure adopted was: ITO / ZnO or LnZnO / QDs / ZnO or LnZnO / Al, and the single-carrier device (hole) structure (marked as Hole): ITO / PEDOT:PSS / TFB / QDs / Au.
[0125] The JV characteristic test of the above single-type carrier device is carried out, and the JV characteristic curve obtained by the test is as follows: Fig.18 shown.
[0126] According to the Mott-Gurney formula, under the same applied voltage, the mobility is proportional to the current density. Fig.18 It can be seen that the standard ZnO obtained in Comparative Example 1 has a higher current density than the single carrier (electron) device based on the ZnO-based nano-doped material LnZnO obtained in Examples 1 to 4, that is, the current density of the single carrier (electron) device after doping is closer to the single hole device, and the corresponding ZnO mobility is reduced. This shows that the QLED device based on the ZnO-based nano-doped material LnZnO obtained in Examples 1 to 4 as the electron transport layer can reduce the electron transport capacity, improve the carrier injection imbalance problem where the electron transport is more than the hole, reduce the charging of quantum dots, and improve the radiation recombination efficiency.
[0127] Test Example 2
[0128] In order to explore the influence of the materials provided in Examples 1 to 4 and Comparative Examples 1 to 3 on the fluorescence quenching effect of quantum dots, the following test examples are prepared to facilitate the transient-steady-state fluorescence spectrum test of the present invention. The details are as follows:
[0129] Test Example 1: Using the same anode, light-emitting layer material and electron transport layer material as in Example 5, the light-emitting layer was spin-coated on the surface of the anode using the same spin coating operation as in Example 5, and then the electron transport layer was spin-coated on the surface of the light-emitting layer, recorded as QD / NdZnO (Nd: 10%) (anode + light-emitting layer + sample of Example 1).
[0130] Test Example 2: Using the same anode, light-emitting layer material and electron transport layer material as in Example 5 and the prepared electron transport layer material in Example 2, the light-emitting layer was spin-coated on the surface of the anode using the same spin coating operation as in Example 5, and then the electron transport layer was spin-coated on the surface of the light-emitting layer, recorded as QD / GdZnO (Gd: 1%) (anode + light-emitting layer + sample of Example 2).
[0131] Test Example 3: Using the same anode, light-emitting layer material and electron transport layer material as in Example 5, the light-emitting layer was spin-coated on the surface of the anode using the same spin coating operation as in Example 5, and then the electron transport layer was spin-coated on the surface of the light-emitting layer, recorded as QD / EuZnO (Eu: 5%) (anode + light-emitting layer + sample of Example 3).
[0132] Test Example 4: Using the same anode, light-emitting layer material and electron transport layer material as in Example 5, the light-emitting layer was spin-coated on the surface of the anode using the same spin coating operation as in Example 5, and then the electron transport layer was spin-coated on the surface of the light-emitting layer, recorded as QD / ErZnO (Er: 15%) (anode + light-emitting layer + sample of Example 4).
[0133] Test Example 5: Using the same anode and light-emitting layer materials as in Example 5, the light-emitting layer was spin-coated on the surface of the anode using the same spin-coating operation as in Example 5, which is recorded as QD (anode + light-emitting layer).
[0134] Test Example 6: Using the same anode, light-emitting layer material and the material prepared in Comparative Example 1 as in Example 5, the light-emitting layer was spin-coated on the surface of the anode using the same spin coating operation as in Comparative Example 5, and then the electron transport layer was spin-coated on the surface of the light-emitting layer, recorded as QD / ZnO (anode + light-emitting layer + ZnO in Comparative Example 1).
[0135] Test Example 7: Using the same anode, light-emitting layer material and the material prepared in Comparative Example 2 as in Example 5, the light-emitting layer was spin-coated on the surface of the anode using the same spin coating operation as in Comparative Example 5, and then the electron transport layer was spin-coated on the surface of the light-emitting layer, recorded as QD / Nd2O3ZnO (Nd2O3: 10%) (anode + light-emitting layer + sample of Comparative Example 2).
[0136] Test Example 8: Using the same anode and light-emitting layer materials as in Example 5 and the material prepared in Comparative Example 3, the light-emitting layer was spin-coated on the surface of the anode using the same spin-coating operation as in Comparative Example 5, and then the electron transport layer was spin-coated on the surface of the light-emitting layer, recorded as QD / LaZnO (La: 10%) (anode + light-emitting layer + sample of Comparative Example 3)
[0137] The quantum dot fluorescence quenching effect of the composite board samples provided in Test Examples 1 to 8 of the present invention was tested, and the fluorescence spectra obtained by the test were as follows: Figures 19-20 As shown; among them, Fig.19 is the steady-state fluorescence spectrum, Fig. 20 Transient fluorescence spectrum.
[0138] from Fig.19 , 20It is obvious from the figure that due to the direct contact between ZnO and quantum dots, the lifetime of quantum dots is reduced from 7.5ns to 6.45ns. This shows that the oxygen vacancy defects of ZnO quench the excitons and reduce the lifetime of quantum dots. The effect of test examples 7 and 8 in reducing the fluorescence quenching of quantum dots is far inferior to that of test examples 1 to 4. However, the fluorescence lifetime of quantum dot films spin-coated with different doping ratios of ZnO is significantly increased. Compared with the lifetime of test example 6, the lifetime of test examples 1 to 4 is significantly increased, which is consistent with the reduction of oxygen vacancies in the XPS test, which effectively shows that LnZnO NPs have fewer exciton quenching sites, which is beneficial to improve the radiation recombination efficiency of the quantum dot layer.
[0139] Test Example 3
[0140] (1) Current density-voltage-brightness test
[0141] The QLED devices of Examples 5 to 8 and Comparative Example 4 were subjected to a current density-voltage-brightness test. The current density-voltage-brightness curves obtained by the test are shown in FIG. Fig.21 shown.
[0142] from Fig.21 It is obvious that in the low voltage region, the leakage current of the device with LnZnO material as the electron transport layer is significantly lower than that of the device with standard ZnO as the electron transport layer. Referring to the above XPS and AFM test results, it can be seen that this is because the doping of lanthanide elements reduces the defect state of ZnO and improves the rough morphology of the film, thereby reducing the leakage current and improving the performance of QLED devices.
[0143] (2) Current efficiency-brightness-external quantum efficiency test
[0144] The QLED devices of Examples 5 to 8 and Comparative Examples 4 to 6 were tested for current efficiency-brightness-external quantum efficiency. The current efficiency, brightness, and external quantum efficiency curves obtained by the tests of Examples 5 to 8 and Comparative Examples 4 to 6 are shown in FIG. Fig. 22 The current efficiency, brightness and external quantum efficiency of Examples 5 to 8 and Comparative Examples 4 to 6 are shown in Table 1.
[0145] Table 1
[0146]
[0147] from Fig. 22As can be seen from Table 1, the external quantum efficiency of the QLED devices in Examples 5-8 has been significantly improved. Among them, when the Nd doping ratio is 10%, the Gd doping ratio is 1%, the Eu doping ratio is 5%, and the Er doping ratio is 15%, the device performance has been maximally improved. Referring to the test results such as UPS and single-carrier device tests above, it shows that the band gap of lanthanide-doped ZnO is slightly increased compared with ZnO, the conduction band position is shifted downward, and the carrier mobility is reduced. Thus, to a certain extent, its electron transport ability is weakened, making the carrier injection in the device more balanced, and further effectively reducing the fluorescence quenching of ZnO to QDs.
[0148] (3) Lifetime efficiency decay test
[0149] The lifetime efficiency decay tests were carried out on the QLED devices of Examples 5-8 and Comparative Examples 4-6. The lifetime decay curves obtained from the tests of Examples 5-8 and Comparative Example 4 are as Fig.23 shown.
[0150] Under the constant current mode with basically the same initial brightness, the device lifetime was calculated through the lifetime formula L0 n ×T 0.5 = K (where K is a constant, 1 < n < 2), assuming the acceleration coefficient n = 1.5. For the QLED devices of Comparative Examples 4-6 and Examples 5-8 in the present invention, when converted to the T 2 device lifetimes at an initial brightness of 1000 cd / m 95 are 69.74 h, 73.58 h, 82.92 h, 353.77 h, 272.46 h, 154.73 h, and 132.66 h respectively; the T 50 device lifetimes are 1739.79 h, 1835.59 h, 2068.59 h, 8229.93 h, 6539.04 h, 3713.52 h, and 2214.28 h respectively. This shows that, compared with ZnO, the device lifetime improvement of the devices based on the electron transport layers prepared in Comparative Examples 2 and 3 is not obvious. The reason is that the materials prepared in Comparative Examples 2 and 3 are not nanocrystal stacks and do not conduct electricity by intrinsic electrons, and the application in QLED has a poor effect. The device lifetime of the LnZnO electron transport layer prepared by the chemical method is significantly increased.
[0151] In summary, when the Nd doping ratio is 10%, the Gd doping ratio is 1%, the Eu doping ratio is 5%, and the Er doping ratio is 15%, the device performance has been maximally improved. Compared with the device of Comparative Example 4, the brightness of the material obtained in Example 5 has been increased by 48.72%, and the device EQE has been increased from 14.88% to 24.39%, an increase of 63.91%. At the same time, when converted to the initial brightness of 1000 cd / m 2 for the green device prepared in Example 5, the T 50The lifespan is increased to 8229.93 h compared to 1739.79 h of the device in comparative example 4. Therefore, the lifespan of the device based on the material of the present invention is greatly improved.
[0152] The above are only preferred embodiments of the present invention, and are not limited to the above examples. For those skilled in the art, various changes and variations are possible under the principle of the present invention. Any modifications and improvements made should be considered within the scope of protection of the present invention.
Claims
1. A ZnO-based nano-doped material, characterized in that: It comprises ZnO and a lanthanide element doped in the ZnO; the lanthanide element is any one of Nd, Gd, Eu and Er; and the amount of the lanthanide element in the ZnO-based nano-doped material accounts for 1 to 15%.
2. The ZnO-based nano-doped material according to claim 1, characterized in that: The amount of Nd in the ZnO-based nano-doped material accounts for 7-12%, the amount of Gd in the ZnO-based nano-doped material accounts for 1-3%, the amount of Eu in the ZnO-based nano-doped material accounts for 3-8%, and the amount of Er in the ZnO-based nano-doped material accounts for 12-15%.
3. The ZnO-based nano-doped material according to claim 2, characterized in that: The amount of Nd in the ZnO-based nano-doping material is 10%, the amount of Gd in the ZnO-based nano-doping material is 1%, the amount of Eu in the ZnO-based nano-doping material is 5%, and the amount of Er in the ZnO-based nano-doping material is 15%.
4. The method for preparing the ZnO-based nano-doped material according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: uniformly mixing a zinc salt solution and a lanthanide compound solution, then adding an alkali solution to stir and react, and after the reaction is completed, adding a precipitant to the reaction solution and centrifuging to obtain the lanthanide compound; the lanthanide compound is any one of a neodymium compound, a gadolinium compound, a europium compound and an erbium compound.
5. The method for preparing the ZnO-based nano-doped material according to claim 4, characterized in that: The molar ratio of the zinc salt to the lanthanide compound is 99:1 to 85:15; the zinc salt and OH in the alkali solution - The molar ratio is 1:0.5~4.
6. The method for preparing the ZnO-based nano-doped material according to claim 4, characterized in that: The neodymium compound is at least one of neodymium sulfate, neodymium chloride, neodymium nitrate, neodymium acetate, and neodymium acetylacetonate; the europium compound is at least one of europium sulfate, europium chloride, europium nitrate, europium acetate, and europium acetylacetonate; the gadolinium compound is at least one of gadolinium sulfate, gadolinium chloride, gadolinium nitrate, gadolinium acetate, and gadolinium acetylacetonate; the erbium compound is at least one of erbium sulfate, erbium chloride, erbium nitrate, erbium acetate, and erbium acetylacetonate.
7. The method for preparing ZnO-based nano-doped materials according to claim 4, characterized in that: The concentration of the zinc salt solution is 0.01-0.2 mol / L, the concentration of the lanthanide compound solution is 0.01-0.2 mol / L, and the concentration of the alkali solution is 0.1-2 mol / L.
8. The method for preparing ZnO-based nano-doped materials according to claim 4, characterized in that: The zinc salt is any one of zinc acetate, zinc nitrate, zinc chloride, zinc sulfate, zinc acetylacetonate, and zinc gluconate; the solvents of the zinc salt solution and the lanthanide compound solution are any one of dimethyl sulfoxide, ethanol, n-heptane, and ethyl acetate; and the alkali solution is any one of potassium hydroxide solution, sodium hydroxide solution, ammonia water, and tetramethylammonium hydroxide solution.
9. The method for preparing the ZnO-based nano-doped material according to claim 4, characterized in that: The stirring reaction temperature is 10-30° C., and the stirring reaction time is 1-3 hours.
10. A QLED device, characterized in that: The invention comprises, from the lower layer to the upper layer, an anode, a hole injection layer, a hole transport layer, a light-emitting layer, an electron transport layer and a cathode; the electron transport layer is made of the ZnO-based nano-doped material according to claim 1.